Graft-Versus-Host Disease: A Model of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis - Azukizawa, Hiroaki (Current Immunology Reviews (Discontinued), 2014)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse reactions (SCARs) characterized by necrotic changes of the epidermis. Recent studies suggest that skin damage fromSJS and TEN is mediated by cytotoxic granules produced by cytotoxic T-cells. However, the pathogenesis of SJS and TEN is notfully understood. The most severe skin damage from acute graft-versus-host disease (GvHD) after hematopoietic stem cell transplantation is clinically and histopathologically similar to TEN. Therefore, animal models of acute GvHD can reveal details about T-cell-induced SCARs. In this review, the pathogenesis of SJS and TEN is discussed in reference to animal models of keratinocyte-specific skin diseases that are similar to acute GvHD. These models demonstrated that CD8+ cytotoxic T-cells are the essential effector cells of both SJS and TEN, and the loss of suppression by thymus-derived, regulatory T-cells is important for the pathogenesis of TEN. Recently, animal models of SJS and TEN using human samples and drugs were established, providing different aspects of the pathological mechanisms of these diseases.
Keywords: graft-versus-host diseaseregulatory T-cells